STRATEGI ADAPTASI MINORITAS KRISTEN DALAM MENJAGA SIKAP HIDUP TOLERANSI BERAGAMA DI DESA TUNTUNG TIMUR KABUPATEN BOLAANG MONGONDOW UTARA - Thomas, Art Samuel; Mawikere, Marde S.; Thomas, Hengky (Tumou Tou, 2020)
Tolerance is an attitude or behavior that respects and respects all other people's actions as long as the actions are in accordance with the rules and norms in the existing community. The tolerance of fellow human beings can be manifested in the life of religious tolerance. This study aims to: Know the adaptation strategies of Christian minorities in maintaining a life attitude of religious tolerance. This research was conducted in Tuntung Timur Village, Pinogaluman Subdistrict, North Bolaang Mongondow Regency for 3 (three) months, from October to December 2019. This research method was qualitative with the technique of determining the sample / informant was selected by purposive sampling to obtain the required data. The sampling technique is done by snowball sampling. Based on the results of research on social adaptation strategies undertaken by Christian minority communities in maintaining the attitude of religious tolerance, namely: Adaptation Strategies Based on Norms of Life consisting of: 1). Active Participation in the Implementation of Government Programs, 2). Active Participation in Social and Cultural Activities, 3). Active Participation in Majority Community Religious Activities, 4). Active Participation in Religious Harmony Organizations, 5). Religious Services Schedule Not Simultaneous. B). Adaptation Strategies when Situations Change in Society is to increase the spirit of religious harmony, C). Behavior Optimization Strategy to Fit the Conditions in the Community, D). Strategies for the Utilization of Human and Family Resources